The Biochemical Role of Nutrition in the Regulation of Metabolism and Body Health - Aerin Regina Putri; Mirna Adelia Pratiwi Manu (Journal of Nutrition and Health Care, 2026)
Nutritional biochemistry is a branch of science that studies the relationship between the chemical structure of nutrients and their biological functions in the body. Nutrients, including carbohydrates, proteins, fats, vitamins, and minerals, play a role in metabolic processes, energy formation, and regulation of physiological functions. This article discusses the biochemical role of nutrients in supporting the body's metabolism and maintaining health, focusing on enzymatic mechanisms, metabolic pathways, as well as the use of nutritional biomarkers for nutritional status evaluation. An in-depth understanding of the biochemical aspects of nutrition helps in the development of effective diet, supplementation, and health intervention strategies.